2018
DOI: 10.1017/s175577391800022x
|View full text |Cite
|
Sign up to set email alerts
|

Sharing is caring: the role of voter-candidate similarities in intra-party electoral competition

Abstract: Previous studies have found similarities with presidential candidates or party leaders to be an important factor in explaining voting behaviour. However, with the exception of gender, few studies have structurally studied voter-candidate similarities in intra-party electoral competition. This study investigates the Belgian case and argues that voter-candidate similarities play a role in the decision-making process of citizens when casting preferential votes. Moreover, it investigates whether underrepresented g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
2
15
1
2
Order By: Relevance
“…Studies have shown that a wide arrange of PVEAs, such as gender, ethnicity, local experience, media attention, but also physical appearance, all have an influence on the number of preferential votes candidates receive (e.g. Maddens et al, 2006;Marien et al, 2017;van Erkel, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that a wide arrange of PVEAs, such as gender, ethnicity, local experience, media attention, but also physical appearance, all have an influence on the number of preferential votes candidates receive (e.g. Maddens et al, 2006;Marien et al, 2017;van Erkel, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…24 In jedem Fall haben offene Listen an sich auch eine weitere positive Eigenschaft. Sie könnten gleichzeitig und ohne Weiteres auch die Repräsentation von anderen unterrepräsentierten Gruppen wie etwa jüngeren Leuten oder Personen mit Migrationshintergrund fördern (Bloom und Thames 2021;van Erkel 2019). Insgesamt plädieren wir somit dafür, der Einführung offener Listen in der Debatte zur Reform des Wahlrechts mehr Beachtung zu schenken.…”
Section: Werden 23unclassified
“…Sollte ein relevanter Anteil des Elektorats in seiner Parteientscheidung vom Anteil an Kandidatinnen geleitet werden, würden sich die Analysen unter Parteianhänger*innen auf eine durch Selbstselektion verzerrte Subgruppe stützen.In Bezug auf die Wahlentscheidung in offenen Listen hat der vorangehende Abschnitt gezeigt, dass Frauen über Parteigrenzen hinweg Gleichstellungsmaßnahmen stärker befürworten als Männer. In Kombination mit den Ergebnissen aus der Literatur zur bevorzugten Wahl von Kandidat*innen, die dasselbe Geschlecht haben wie die Wähler*innen(Holli und Wass 2010;Giger et al 2014;van Erkel 2019) ergibt sich: Hypothese H 1 Die Wahrscheinlichkeit, dass Frauen für eine Kandidatin stimmen ist höher als die Wahrscheinlichkeit, dass Männer für eine Kandidatin stimmen. Die Analyse der Umfragedaten weist zudem darauf hin, dass es Unterschiede nach der gesellschaftspolitischen Ausrichtung der Parteien gibt -ein Muster, dass sich zudem auch in der internationalen Experimentalanalyse von Golder et al (2017) gezeigt hat: Hypothese H 2 Die Wahrscheinlichkeit, für eine Kandidatin zu stimmen ist unter Wähler*innen gesellschaftspolitisch konservativerer Parteien geringer.…”
unclassified
“…Their reasoning is that these under-represented groups develop a stronger social identity and are therefore more inclined to vote for someone from the in-group. In a recent study van Erkel (2019) is the first to systematically combine voter (demand) and candidate (supply) characteristics in one model, allowing one to better grasp the decision-making process of voters. He establishes that, controlling for structural inequalities between candidates, the effect of a voter sharing the same gender with a candidate on the likelihood of a voter also casting a preference vote for that candidate is indeed stronger for women.…”
Section: Individual-based Characteristicsmentioning
confidence: 99%